The channel catfish genome sequence provides insights into the evolution of scale formation in teleosts - Zhanjiang Liu (Nature Portfolio, 2016)
Catfish represent 6.3% of all vertebrate species, and occupy a phylogenetic position close to the common ancestor of bony fish. Liu et al. present a reference genome of the channel catfish, and reveal a genomic basis for the evolutionary loss of scales in these species.